Applications of Biological and Physiological Signals in Commercial Video Gaming and Game Research: A Review - Hughes, Alayna; Jorda, Sergi (Frontiers in Computer Science, 2021)
This article reviews the use of physiological signals in research and consumer video gaming. Video gaming is now available as a fully immersive experience that creates responsive inputs and outputs in relation to the user, and some experimental developers have integrated the use of the voice, brain, or muscles as input controls. Researchers have also been exploring the benefits of using physiological sensing devices in their game-based research. They have experimented with brain-controlled gaming for stress control and used biosignals to retrieve emotional and interaction information from users during gameplay. They have also integrated biosensors into games to aid in physical rehabilitation as well as the treatment of some attention and neurological disorders. This paper will discuss recent trends and possible future uses of biosignals as input and output in the field of video game-based research.